STUDI ADSORPSI ION LOGAM Pb(II), Cu(II), DAN Cr(III) MENGGUNAKAN ABU DASAR BATUBARA - , ANIES SEPTIANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Heavy metals removal from aqueous solution using coal bottom ash as an adsorbent which is thewasteof coal combustionfrom thePS. Madukismo, PT.MadubaruYogyakarta has been studied. The aim of this research was to examine the ability of bottom ash in adsorbing mixture of metal ions. The research consisted of characterization andidentification ofthe componentscontained incoalcombustionwaste using FTIR and XRD. The process of adsorption Pb(II), Cu(II), and Cr(III) metal ionswas done byadding theadsorbent into the solutionmixture. The unabsorbed heavy metal was determined by Atomic AbsorptionSpectrophotometer. The influences of mass, also pH solution, time of adsorption and initial concentration of heavy metal ions have been studied. The results of this research showedthatcoalcombustionwastesin the form ofbottom ashis composed ofSiO2andAl2O3 as the major components. The highest adsorption of 15 mL solution containing Pb(II), Cu(II), and Cr(III) metal ions with 50 mg/L of each concentration can be obtained using0.2gadsorbentfor 60 minutes.The adsorption of Pb(II), Cu(II), and Cr(III) metal ions was fitted by Pseudo second order model, with the adsorption rate constant was0.031 mgg -1 min - 1 forPb(II) metal ion, 0.418mgg -1 min -1 forCu(II) metal ion, and 0.094 mgg -1 min -1 for Cr(III) metal ions. From the isotherm study, Langmuir isotherm model was found to be the best fit for thissystem, withthe adsorptioncapacityof0.031